Addition of Polyurethane in the reformation of Bitumen - abroumand, Maryam; Rahimi Domakani, Ebrahim; Parvaneh, Sajad (Revista Publicando, 2018)
In the current research, the addition of Polyurethane in the process of reforming the Bitumen has been investigated. The construction engineers are concern about the asphaltic damages and consume too much money in order to maintenance of asphaltic roads. There are many efforts in order to enhance the resistance and the age of asphalt including the improvement of Bitumen”™s characteristics. It is common to use polymers in order to reform the Bitumen”™s characteristics. Thermoplastic Elastomers and reactive polymers are the families of polymers which have impressive effects on the characteristics of Bitumen. TPU and PU were used as modifier additive in Bitumen. Bitumen penetration test, softening point, TFO, PAV,DSR,BBR and FTIR on the modified samples with different forms of Polyurethane have been done in the current research. The achieved findings showed that Polyurethane decreased the penetration degree and even it increases the softening point of Bitumen. The mentioned modified Bitumen had the following characteristics: high viscosity and less sensitivity. Polyurethane also has increased the temperature of base Bitumen”™s performance and its resistance towards the transformation. In an average temperature, the modified Bitumen has better performance than fatigue of base Bitumen. Although the Polyurethane has a little positive effect on the Bitumen”™s performance, it couldn”™t add any positive performance to Bitumen in low temperature. The results of FTIR test showed, the Polyurethane bonds determined the chemical structures.